Analisis Financial Distress dengan Menggunakan Model Grover pada Perusahaan Sektor Property, Real Estate dan Kontruksi - Firhan Dwi Januar; Nor Norisanti; Faizal Mulia (BUDGETING : Journal of Business, Management and Accounting, 2020)
This study aims to determine the Grover model that can predict Financial Distress in the property, real estate and construction sector companies listed on the IDX, namely PT. Alam Sutera Realty Tbk, PT. Cowell Development Tbk, PT. Intiland Development Tbk. This study uses descriptive analysis techniques with a quantitative approach to systematically describe predictions of Financial Distress of a company. The results showed that the three companies had a score of more than or equal to 0.01 (G 1 0.01) within 3 years with details, in 2015 PT. Alam Sutera Realty Tbk obtained a score of 0.430, 2016 obtained a score of 0.405, and in 2017 obtained a score of 0.473. PT. Cowell Development Tbk in 2015 obtained a score of 0.198, in 2016 obtained a score of 0.345, and in 2017 obtained a score of 0.368. while PT. Intiland Development Tbk in 2015 obtained a score of 0.661, 2016 obtained a score of 0.610, and in 2017 obtained a score of 0.554. Conclusions based on the results of the study show that the three companies did not experience Financial Distress because all company scores exceeded the score limit determined by the Grover model, in the sense that the company is in a healthy state. Keywords: Financial Distress, Grover model